An exploration of pre-performance routines, self-efficacy, anxiety and performance in semi-professional soccer - Denise Hill (European Journal of Sport Science, 2014)
Whilst much research has suggested a positive link between pre-performance routines (PPRs) and performance, the specific mechanisms of the process have yet to be understood fully. It has been suggested that the PPR may influence performance through lowering the athlete's anxiety, and/or increasing their self-efficacy, but to date this has not specifically been explored in detail. As a result the aim of the current study was to explore the impact of specific individualised PPRs on performance, anxiety and self-efficacy in semi-professional soccer players. Participants were 20 male semi-professional soccer players (M = 19.45, SD = 2.81) recruited from clubs in England. Adopting a repeated measure design, players were tested on performance, anxiety, and self-efficacy pre- and post a 7-day intervention period in which the participants learnt a new PPR. The data were analysed using factorial mixed measures analysis of variance (ANOVAs), with the results revealing a significant difference in somatic anxiety for the experimental group and a decrease in performance for the control group. The study provides further support for the suggestion that the PPR can enhance performance by reducing experiences of anxiety prior to performance.